Breathing Exercises terhadap Kecemasan pada Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis - Laoli, Zoniawan; Butar-butar, Friska; Halawa, Afeus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of breathing exercises on anxiety in chronic kidney failure patients undergoing hemodialysis. The method used is a quasi experiment with a two group approach: control group and intervention group pretest-posttest. Data were processed using Wilcoxon and Mann Whitney. The results showed that there was an effect of breathing exercises on anxiety (p value 0.000) and there was a significant difference between the control group and the intervention group (p value 0.000). In conclusion, there is an effect of breathing exercises on anxiety and there is a significant difference between the control group and the intervention group. Keywords: Breathing Exercises, Anxiety, Chronic Kidney Disease